Factors Affecting Mothers in Giving Vitamin A Capsules To Toddlers - Ingka Kristina Pangaribuan (Universitas Aisyah Pringsewu, 2022)
Vitamin A is one of the nutrients from the vitamin group that is needed by the body which is useful for eye health (so you can see well) and for body health (increasing the body's resistance to fight diseases such as measles, diarrhea, and other infectious diseases). According to the World Health Organization (WHO), as many as 250 million preschool children experience vitamin A deficiency events, with an estimated annual incidence of blindness of 250,000 to 500,000 children (1% -2%), and within 12 months half of children died as a result of vitamin A deficiency (WHO, 2019). This study aims to determine the factors influencing mothers giving vitamin A capsules to toddlers at UPT Puskesmas Bahorok, Langkat Regency in 2021. The type of research is an analytical survey with a cross-sectional study approach. The population is all mothers with toddlers UPT Puskesmas Bahorok Langkat Regency in 2021 totaling 248 people. The number of samples used was 62 people obtained using the 25% Arikunto formula. Data analysis technique using chi-square. The results showed that 62 respondents were mothers who had toddlers, the results showed that the majority of respondents had good knowledge, 37 respondents (59.7%) and a minority of respondents who had bad knowledge, 25 respondents (40.3%), had higher education, 34 respondents (54.8%) ) and a minority of respondents with low education as many as 28 respondents (45.2%), a negative attitude as many as 32 respondents (51.6%) and a minority of respondents who had a positive attitude as many as 30 respondents (48.4%), and gave Vitamin A capsules as many as 32 respondents (51.6%) and a minority of respondents did not provide Vitamin A Capsules. As many as 30 respondents (48.4%) and there was a relationship between mother's knowledge (0.000), mother's education (0.003), attitude (0.01) in giving Vitamin A capsules In Toddlers. It is suggested to the public to be able to pay attention, add insight about giving vitamin A to toddlers so that the need for vitamin A can be fulfilled according to age. Abstrak: Vitamin A adalah salah satu zat gizi dari golongan vitamin yang sangat diperlukan oleh tubuh yang berguna untuk kesehatan mata (agar dapat melihat dengan baik) dan untuk kesehatan tubuh (meningkatkan daya tahan tubuh untuk melawan penyakit misalnya campak, diare dan penyakit infeksi lain). Menurut World Health Organization (WHO) sebanyak 250 juta anak pra-sekolah mengalami kejadian kekurangan vitamin A, dengan jumlah angka kejadian anak yang mengalami kebutaan setiap tahun diperkirakan 250.000 sampai 500.000 (1%-2%), serta dalam jangka waktu 12 bulan separuh anak meninggal akibat dari kekurangan vitamin A (WHO, 2019). Penelitian ini bertujuan untuk mengetahui Faktor-Faktor Yg Mempengaruhi Ibu Dalam Pemberian Kapsul Vitamin A Pada Balita di UPT Puskesmas Bahorok Kabupaten Langkat Tahun 2021. Jenis penelitian merupakan survey bersifat analitik dengan pendekatan cross sectional study. Populasi adalah seluruh ibu yang memilliki balita UPT Puskesmas Bahorok Kabupaten Langkat Tahun 2021 berjumlah 248 orang. Jumlah sampel yang digunakan adalah 62 orang yang diperoleh dengan menggunakan rumus arikunto 25%. Teknik analisis data menggunakan chi square. Hasil penelitian bahwa 62 responden ibu yang memiliki balita, didapatkan hasil mayoritas responden berpengetahuan Baik sebanyak 37 responden (59,7%) dan minoritas responden berpengetahuan tidak baik 25 responden (40,3%), berpendidikan tinggi sebanyak 34 responden (54,8%) dan minoritas responden berpendidikan rendah sebanyak 28 responden (45,2%), sikap negatif sebanyak 32 responden (51,6%) dan minoritas responden memiliki sikap positif sebanyak 30 responden (48,4%), dan memberikan kapsul Vitamin A sebanyak 32 responden (51,6%) dan minoritas responden tidak memberikan Kapsul Vitamin A Sebanyak 30 responden (48,4%) serta ada hubungan pengetahuan ibu (0,000), pendidikan ibu (0,003), sikap (0,01) dalam pemberian kapsul Vitamin A Pada Balita. Disarankan kepada masyarakat untuk dapat memperhatikan, menambah wawasan tentang pemberian vitamin A pada balita sehingga kebutuhan vitamin A dapat tercukupi sesuai dengan usia.